Implementation and evaluation in low intensity intervention programs from the CONNECT perspective of mixed methods: Application in a case of an autistic child - Arias-Pujol, Eulàlia; Mestres, Marina; Miralbell, Júlia; Bachs, Natalia; Anguera, M. Teresa (Frontiers in Psychology, 2022)
There has been a comprehensive development over the last few years of low intensity intervention programs that are implemented within a user context and that are made up of everyday life activities, and it has been necessary to adapt the necessary methodological channels in order to guarantee an adequate resolution pathway. The mixed method perspective offers a suitable framework, and observational methodology – in itself considered mixed method – is appropriate for studying the implementation and evaluation of low intensity intervention programs, allowing the development of the QUAL-QUAN-QUAL stages that correspond to the connect integration pathway of mixed methods. In this work it was applied to a single case, in a low intensity intervention, retrieving valuable information obtained, but systematizing it and applying quantitizing to the qualitative data that was treated quantitatively in a rigorous manner. The aim was to analyze the psychotherapist-patient interaction in psychoanalytic psychotherapy, in which we sought to identify which of the therapist’s techniques stimulated actions of reciprocal social interaction in the child, and which techniques inhibited non reciprocal social interactions. The observational design was nomothetic, follow-up, and multidimensional. The patient was a 4-year-old boy with a diagnosis of severe autism spectrum disorder. We used an ad hoc observation instrument combining a field format and a category system. Interobserver agreement was analyzed quantitatively by Cohen's kappa using the free QSEQ5 software program. Polar coordinate analysis was carried out using the free program HOISAN 2.0. Polar coordinate analysis allows us to obtain an inter-relational map of the connections detected between focal behavior established in each case and the different categories. The results provide objective evidence – backed up by the application of polar-coordinate-based data analysis – that within a framework of psychoanalytic psychotherapy, the techniques of “verbalization” and “vocalization” significantly activate reciprocal social interaction behaviors and inhibit non social reciprocal behaviors in a child with severe ASD with no language. On the other hand, direct gaze promotes the child’s withdrawal. The results are of key importance as they show the therapist behaviors most useful for promoting social interaction in a child with severe autism.